ECONOMIC JOINT COST THEORY AND ACCOUNTING PRACTICE. - Manes, R. P.; Smith, Vernon L. (The Accounting Review, 1965)
One of the continuing unsolved problems of accounting is that of joint costs of production. Generations of accountants have struggled in the definitional morass of joint products, major products, co-products, minor products, by-products, and scrap, waste, spoiled or defective products. For their part, economists have been quick to point out that, in many cases, cost allocations to joint products are arbitrary and thus unjustified. Be that as it may, for a number of mundane reasons well known to accountants, such as the preparation of balance sheets and income statements, evaluation of inventories, preparation of tax returns and public regulation. Some allocations are required and must be made. It proposes to relate accounting to economic theory and in so doing to make a very limited advance on the problem. In a joint cost situation, one input serves to produce two or more products, these two or more outputs may issue from the production process either in fixed proportions or in variable proportions.